Laudacja dla Andrzeja Wajdy - Popiel, Jacek (Przestrzenie Teorii, 2017)
During the laudation speech on 12th May 2016 at the Jagiellonian University Senate session on the occasion of Andrzej Wajda being awarded the gold medal Plus Ratio Quam Vis, the director’s most significant services to Polsh and world culture (film, theatre, museum art) were presented.